1988
DOI: 10.1073/pnas.85.16.6092
|View full text |Cite
|
Sign up to set email alerts
|

Anti-idiotypic antibodies that react with microtubule-associated proteins are present in the sera of rabbits immunized with synthetic peptides from tubulin's regulatory domain.

Abstract: A fundamental question in microtubule research is how the interactions of tubulin subunits with microtubule-associated proteins (MAPs) are controlled. The answer should provide insight into the regulation of the cellular processes in which microtubules are implicated. Previous work demonstrated the interaction ofMAPs with a 4-kDa C-terminal domain of tubulin a and 13 subunits. Synthetic peptides from the variable region of the 4-kDa C-terminal moiety of tubulin subunits, a-(430-441) and 13-(422-434), bind to M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Each of the proposed acidic N-terminal, basic middle, and microtubule-binding C-terminal domains ( (27). Anti-idiotype antibodies isolated from sera after immunization with these peptides also bound to tau and MAP2 and interfered with their ability to promote microtubule assembly in vitro (34). This result suggests that MAP2 might also contain similar microtubulebinding domains which may have evolved by shuffling of exons encoding commonly used functional domains, as was suggested for many other proteins (18,40).…”
Section: Resultsmentioning
confidence: 68%
“…Each of the proposed acidic N-terminal, basic middle, and microtubule-binding C-terminal domains ( (27). Anti-idiotype antibodies isolated from sera after immunization with these peptides also bound to tau and MAP2 and interfered with their ability to promote microtubule assembly in vitro (34). This result suggests that MAP2 might also contain similar microtubulebinding domains which may have evolved by shuffling of exons encoding commonly used functional domains, as was suggested for many other proteins (18,40).…”
Section: Resultsmentioning
confidence: 68%
“…The current analysis has therefore excluded this peptide (Fig. l), although it includes the MAP2/tau binding site [e.g., Rivas et al, 1988;Vera et al, 19891 and a neuronal P,-tubulin isotype-specific phosphorylation site [Diaz-Nido et al, 19901. Structure prediction has indicated that the C-terminal peptide (1x414-447 and P:403-443) is folded to form a coiled coil [Lupus et a]., 19911: the marked heterogeneity from ~4 4 1 and P:431 suggests that the prob- (A) The amino acid sequence, in single letter code, of mouse a l , chick PI, and Aspergillus nidulans y-tubulin.…”
Section: Introductionmentioning
confidence: 99%
“…The 20,000 x g pellet was resuspended in electrophoresis sample buffer (32) and fractionated by SDS/polyacrylamide gel electrophoresis (32). Proteins were transferred electrophoretically to nitrocellulose membranes (33) and probed with the antipeptide antibody mdr (Ab-1) (Oncogene Science, Manhasset, NY). This is a rabbit, affinity-purified polyclonal antibody raised against the peptide Cys-Ala-Leu-Asp-Thr-GluSer-Glu-Lys-Val-Val-Gln-Glu-Ala-Leu-Asp-Lys-Ala-ArgGlu-Gly from the C-terminal region of P glycoprotein.…”
mentioning
confidence: 99%